Screening for high bromelain content in different species of pineapple in Malaysia - Zulkipeli, Nur Lina (2007)
Bromelain in pineapple is known for it medical properties such as: Anti-inflammation agent, Effective in relieving inflammation associated with infection and physical injuries. Help to promote and maintain proper digestion, Relieve symptom of stomach upset or heartburn.